Islamic Banking - Value Added Intellectual Coeficient (IB-VAIC) as an Intellectual Capital Proxy Indonesian Islamic Banking - Ema Pratiwi; Rahmad Kadry (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2014)
The main idea of this research is to make the concept of intellectual capital as the most valuable intangible assets for the company. Basically, tangible assets which is owned by the company is also controlled by humans. This study offers Islamic Banking-Value Added Intellectual Coefficient (IB-VAICTM) modified the model pulic by Ulum (2013) as a performance measurement of intellectual capital of Islamic banking in Indonesia. This study also makes Islamic banks rank in term of Best Performance Index (BPI) which is measured using IB-VAIC™. The data used are annual reports, particularly financial performance and balance sheet, obtained either through the official website of each bank as well as from BI website. This study finds that during the study period (2010-2014), the overall performance of Islamic banking in Indonesia in the category of